Hydro-geophysical investigation of groundwater resources potential in Dashti-e-Archi alluvial aquifer, Northeastern Afghanistan - Rohullah Sediqi; Mansoor Mudaser; Vladimir B. Zalishchak; Abdulhalim Zaryab (Results in Earth Sciences, 2025)
Groundwater is the primary source of water for drinking, domestic use, and agricultural in northern Afghanistan. However, due to over four decades of political instability, the region’s groundwater resources remain poorly understood. Identifying optimal locations for water supply schemes considering both quantity and quality is further complicated by the widespread presence of fine-grained materials. This study employed vertical Electrical Sounding (VES) using the Schlumberger configuration in the village of Arbab Rahim Dolat Zai, located in the Dasht-e-Archi district of Kunduz Province. The VES data were interpreted using IPI2Win and ZONDIP1D software. Among the surveyed sites, only the VES1 was identified as optimal, enabling consistent drilling penetration through all five geo-electric layers. Of the five strata, the fourth located at depths of 33–120 ± 10 m and composed primarily of sand, silt and gravel interbedded with clay were recognized as the principal aquifers. These findings were corroborated by lithological logs, validating the reliability of the geophysical interpretations. Additionally, the Thiem and Dupuit equations were applied to analyses steady-state groundwater flow, facilitating the estimation of hydraulic conductivity and transmissivity. The results provide valuable insights to support policymakers and engineers in the sustainable and effectively management groundwater resources in northern Afghanistan.